Forgiveness as a Mediator of Neuroticism and Subjective Well-Being Among University Students in Yogyakarta, Indonesia - Nashori, Fuad; Diana, Raden Rachmy; Saputri D, Leonita Ikasari; Subandi, Subandi; Aziz, Rahmat (Universitas Islam Indonesia, 2024)
This research is intended to determine the role of the personality traits of neuroticism and forgiveness on the psychological well-being of students. The research subjects were active students at various universities in the Special Region of Yogyakarta, Indonesia. The method used is a quantitative method. Data were collected using the Personality Scale, Neuroticism subscale, Forgiveness Scale, and SPANE, and SWLS. Data were analyzed using Structural Equation Modeling (SEM). The research hypothesis is that forgiveness acts as a mediator in the relationship between the personality trait of emotional stability and students' subjective well-being. The results of the research show that the neuroticism variable plays a role in the forgiveness variable with a standardized regression coefficient value of -0.569 and a significance of p = 0.000 (p < 0.05), the forgiveness variable plays a role in the subjective well-being variable with a standardized regression coefficient value of 0.264 and a significance of p = 0.000 (p < 0.05), and the neuroticism variable plays a role in the subjective well-being variable with a standardized regression coefficient value of -0.485 and a significance of p = 0.000 (p < 0.05).